Wireless monitoring prototype for photovoltaic parameters - Sabry, A. H.; Hasan, W. Z. W.; Ab. Kadir, MZA; M. Radzi, M. A.; Shafie, S. (Institute of Advanced Engineering and Science, 2018)
Photovoltaic (PV) parameters monitoring is very important for the implementation and optimum utilization of solar energy as the electricity source. This work proposes a design of simple, cost-efficient, and low consumption wireless PV monitoring system enhanced by a driving software for recording the PV system parameters. The circuit is designed with a minimum number of components to manage four types of sensors to measure four parameters that are essential for real-time analysis and prediction of PV performance. The only pair of XBee RF modules as an active component, while others are passive, includes resistors and capacitors for PV current, and voltage those for signal conditioning, temperature and irradiance sensors were also involved. The paper presents a prototype system for high voltage series-connected PV array in the range (100-310) V and 3 ampere as a maximum current, while the sampling frequency can be configured up to 14 sample/Sec in applications of the short period for data logging for the four channels. The proposed system succeeds in providing real-time monitoring with lower cost and can be extended for more functions such as controlling tracking system and failure diagnosis. Photovoltaic (PV) parameters monitoring is very important for the implementation and optimum utilisation of solar energy as electricity source. This work proposes a design of simple, cost-efficient, and low consumption wireless PV monitoring system enhanced by a driving software for recording the PV system parameters. The circuit is designed with a minimum number of components to manage four types of sensors to measure four parameters that are essential for real-time analysis and prediction of PV performance. Only pair of XBee RF modules as an active components, while othera are passive, includes resistors and capacitors for PV current, and voltage those for signal conditioning, temperature and irradiance sensors were also involved. The paper presents a prototype system for high voltage series connected PV array in the range (100-310) V and 3 ampere as a maximum current, while the sampling frequency can be configured up to 14 sample/Sec in applications of the short period for data logging for the four channels. The proposed system succeeds in providing real-time monitoring with lower cost and can be extended for more functions such as controlling tracking system and failure diagnosis.